STRATEGI PEMANFAATAN JERAMI PADI SEBAGAI PAKAN SAPI POTONG DI KECAMATAN LIBURENG KABUPATEN BONE: PENDEKATAN ANALISIS SWOT : STRATEGY OF UTILIZING RICE STRAW AS BEEF CATTLE FEED IN LIBURENG DISTRICT, BONE REGENCY: SWOT ANALYSIS APPROACH - Rahmadani, Andi; Wijaya, Andis; Maharani, Nur Fadillah; Amas, Akmal Fikri; Akbar, Andi Muh; Syamsu, Jasmal Ahmari (Universitas Boyolali, 2025)
This study aims to analyze strategies for utilizing rice straw as feed for beef cattle in Libureng District, Bone Regency. The research used a descriptive quantitative approach with a SWOT analysis. Data were obtained from previous studies, expert interviews, and analyses using the IFE, EFE, SWOT, and QSPM matrices. The results showed a total IFE score of 2.75, with key strengths including a high interest in cattle farming among the productive-age population and knowledge of disease prevention. The total EFE score reached 3.00, with the main opportunities being the increasing interest in livestock technology and the demand for quality feed. From the nine alternative strategies identified, the priority strategies based on the QSPM analysis are income diversification through developing processed livestock products (TAS = 6.85) and a feed system based on local forages and agricultural waste (TAS = 6.8). These findings indicate that rice straw holds significant potential not only as a feed source but also as a means to increase income and improve the sustainability and efficiency of livestock farming.